Inhibition of tumor necrosis factor receptor 1 and the risk of periodontitis - Alayash, Zoheir; Baumeister, Sebastian-Edgar; Holtfreter, Birte; Kocher, Thomas; Baurecht, Hansjörg; Ehmke, Benjamin; Reckelkamm, Stefan Lars; Nolde, Michael (Frontiers in Immunology, 2023)
Aim: To investigate the effect of genetically proxied inhibition of tumor necrosis factor receptor 1 (TNFR1) on the risk of periodontitis. Materials and methods: Genetic instruments were selected from the vicinity of TNFR superfamily member 1A (TNFRSF1A) gene (chromosome 12; base pairs 6,437,923–6,451,280 as per GRCh37 assembly) based on their association with C-reactive protein (N= 575,531). Summary statistics of these variants were obtained from a genome-wide association study (GWAS) of 17,353 periodontitis cases and 28,210 controls to estimate the effect of TNFR1 inhibition on periodontitis using a fixed-effects inverse method. Results: Considering rs1800693 as an instrument, we found no effect of TNFR1 inhibition on periodontitis risk (Odds ratio (OR) scaled per standard deviation increment in CRP: 1.57, 95% confidence interval (CI): 0.38;6.46). Similar results were derived from a secondary analysis that used three variants (rs767455, rs4149570, and rs4149577) to index TNFR1 inhibition. Conclusions: We found no evidence of a potential efficacy of TNFR1 inhibition on periodontitis risk.